2020
DOI: 10.33215/sjom.v3i3.334
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Justice and Employee Sustainability: The Mediating Role of Organizational Commitment

Abstract: Purpose- The primary purpose of the study is to determine the impact of organizational justice (OJ) on employee sustainability. Along with that, it also describes how organizational commitment mediates this direct relationship. This study includes all dimensions of OJ which are distributive, procedural and interactional (interpersonal & informational) within the context of a developing country (Pakistan). Design/Methodology- This study has considered employees working in the banking sector of Pakistan. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The essence of organizational commitment lies within the truth that committed employees are highly involved in interlinked behaviors such as innovation performance [72], and enhance the performance and productivity of the firms [73]. Organizational commitment significantly correlates with organizational justice and employee sustainability [74], job behavior, employee fitness, welfare and turnover intentions [71], and especially, with innovation performance [68,69,75].…”
Section: Relationship Between Organizational Commitment and Innovation Performancementioning
confidence: 99%
“…The essence of organizational commitment lies within the truth that committed employees are highly involved in interlinked behaviors such as innovation performance [72], and enhance the performance and productivity of the firms [73]. Organizational commitment significantly correlates with organizational justice and employee sustainability [74], job behavior, employee fitness, welfare and turnover intentions [71], and especially, with innovation performance [68,69,75].…”
Section: Relationship Between Organizational Commitment and Innovation Performancementioning
confidence: 99%
“…It has been proven, for example, that in the case of hotel staff, procedural justice influences turnover intention [34]. The results also showed that organizational justice has an important effect on sustainable employee development, builds motivation, and benefits business as a result [35][36][37]. Sustainable development is considered to be one of the main categories describing the modern world [38].…”
Section: Discussionmentioning
confidence: 99%
“…The consciousness of the outlays of leaving the firm denotes continuance commitment, and assumed responsibility to hold in the firm denotes normative commitment (Meyer et al, 2002). OC has a significant correlation with other concepts such as service sustainability (Fatima et al, 2020), employee vigor and behavior, leaving intents and welfare (Meyer et al, 2002), employee turnover (Mathieu et al, 2016) and IP (Musawa and Ahmad, 2018;Rypestøl and Aarstad, 2018;Zhai et al, 2018). Employees' commitment is allied with the individual (Riaz, 2010) and organizational consequences (Rashid et al, 2003).…”
Section: Literature Review and Relationship Buildingmentioning
confidence: 99%